Deep waters - Larry, H. I. (Zac Power, 2008)
Twelve-year-old Zac sets out on his first solo mission as a spy for the Government Investigation Bureau, piloting an amphibious submersible in hopes of preventing enemies from accessing a top-secret transmitter 4,000 feet below the ocean's surface.